Approximation by Complex Baskakov-Szász-Durrmeyer Operators in Compact Disks (Analysis in Theory and Applications, 2017)
In this paper, we deal with the complex Baskakov-Szász-Durrmeyer mixed operators and study Voronovskaja type results with quantitative estimates for these operators attached to analytic functions of exponential growth in $\mathbb{D}_R=\{z∈\mathbb{C};|z|
Keywords: Complex Baskakov-Szász-Durrmeyer operators; Voronovskaja type result; exact order of approximation in compact disks; simultaneous approximation.